The Effects of the Coating Materials Ratio on the Characteristics of Encapsulated Red Beet Extract - Maskurin, Quinnike Aisy; Septiafianti, Niar; Fitriah, Arsinah Habibah; Widyaningsih, Tri Dewanti; Mubarok, Ahmad Zaki (The Journal of Experimental Life Science, 2026)
Food products with beneficial health effects are increasingly attracting public interest, in line with growing health awareness. Red beetroot (Beta vulgaris L.) is one such food that contains many bioactive compounds and exhibits high antioxidant activity. However, the bioactive compounds in red beetroot are susceptible to degradation, leading to color fading, reduced antioxidant capacity and bioavailability, and shorter shelf life during processing and storage. To enhance their stability, a microencapsulation process using specific coating materials can be applied. This study optimized the wall-material ratio for spray-drying beetroot extract microcapsules, prioritizing the stability/retention of bioactives, encapsulation efficiency, and instant solubility. Microcapsules were produced with soy protein isolate (SPI) : maltodextrin (MD) ratios of 0:1, 1:3, 3:7, 2:3, and 1:1 at a total wall concentration of 10% (w/w) using spray-drying under fixed conditions, inlet temperature 150°C; outlet temperature 82°C; feed rate 5.1 mL·min⁻¹. Betalains were quantified spectrophotometrically; total phenolics by Folin–Ciocalteu; total flavonoids by the aluminum-chloride method; and antioxidant activity by DPPH. Encapsulation efficiency was calculated as the ratio of retained betalains to the initial amount. Microencapsulation of red beet extract using soy protein isolate (SPI) and maltodextrin (MD) as wall materials significantly affected the physicochemical and functional properties of the microcapsules. Antioxidant activity, flavonoid content, phenolic compounds, and encapsulation efficiency increased when SPI and MD were combined at a 1:1 ratio.